Novel polymorphism at ARHGAP24 gene and its association with growth traits in Hu sheep - Huili Shan; Liang yong Guo; Xin Huang; Xiaowei Zhang; Yongqing Jiang; Sangang He; Junfang Jiang (Animal Biotechnology)
It is essential to identify potential genes and genetic variants associated with growth traits to enhance sheep breeding. Previous studies have suggested that the Rho GTPase-activating protein 24 (ARHGAP24) gene may influence the growth of some animals. However, no association has been established between polymorphisms in the ARHGAP24 gene and sheep growth traits. In this study, single-nucleotide polymorphisms (SNPs) in the ARHGAP24 gene of Hu sheep were detected, and functional SNPs associated with Hu sheep growth traits were identified. Twenty-six SNPs were discovered in Hu sheep. Association analysis revealed NC_056059.1:g.455981A > G was significantly associated with average daily gain from six months to one year of age, while NC_056059.1:g.456083 A > G was significantly associated with average daily gain from weaning to six months of age. The relative fluorescence activity (firefly luciferase and sea kidney luciferase) of haplotype GGGG was significantly lower than that of haplotypes GGAA, AAAA and AAGG. Furthermore, ARHGAP24 mRNA expression in the longissimus dorsi muscle of six-months-old sheep was significantly lower than birth sheep. The results showed that NC_056059.1:g.455981A > G and g NC_056059.1:g.456083A > G of ARHGAP24 gene were related to some growth traits of Hu sheep, and ARHGAP24 mRNA was differentially expressed in longissimus dorsi muscle of Hu sheep at different months of age, which could be used as a candidate gene for molecular marker-assisted selection of Hu sheep.